Analysis of Egg Productivity in Buras Chickens Fed Fermented Feed with Various Bioactivators - Dini Julia Sari Siregar; Warisman (Yayasan Sinergi Multidimensi Kreatif, 2026)
This study aimed to analyze the egg productivity of native chickens fed fermented feed using different bioactivators. The primary issue underlying this study was the relatively low egg productivity of indigenous chickens in Indonesia, which ranges from 60 to 120 eggs per hen per year, as well as the high cost of conventional feed, accounting for approximately 60–70% of total production costs. As an alternative solution, a bioconversion technology in the form of feed fermentation was applied to break down the crude fiber bonds in rice bran and corn, improve feed quality and crude protein content, reduce antinutritional compounds, and enhance nutrient digestibility in the digestive tract of chickens. The experiment was conducted using a field laboratory approach based on a non-factorial Completely Randomized Design (CRD) consisting of four dietary treatments with five replications. Each experimental unit contained three 7-month-old native laying hens, resulting in a total of 60 experimental birds. The basal diet consisted of corn (51%), rice bran (30%), soybean meal (10%), fish meal (3%), cooking oil (2%), limestone (1%), and mineral mix (3%). The diet was mixed with selected bioactivator solutions and palm sugar, followed by anaerobic incubation for an optimum fermentation period of 4–7 days. The observed parameters included daily feed intake, daily egg production expressed as Hen Day Production (HDP), average egg weight, and feed efficiency measured by Feed Conversion Ratio (FCR). The collected data were analyzed using Analysis of Variance (ANOVA) to determine the significance of treatment effects. The results demonstrated that fermented feed supplemented with the Starbio bioactivator (P3) produced the most favorable performance, resulting in the highest HDP (54.80%), the greatest average egg weight (46.50 g), and the lowest FCR (3.13), indicating the highest feed efficiency. These findings are expected to provide a scientific basis for smallholder poultry farmers in selecting appropriate commercial bioactivators for producing high-quality fermented feed, thereby reducing feed production costs and supporting the sustainable development of native chicken farming.